2020
DOI: 10.1111/pan.13838
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of catheter‐based patent ductus arteriosus closure in neonates weighing <3 kg: A Retrospective Observational Study

Abstract: Background:The patent ductus arteriosus is a cardiac lesion commonly found in premature neonates. Though surgical closure via thoracotomy is the most definitive treatment option, it is associated with significant morbidity. New catheter-based closure options offer a potentially safer alternative treatment, even in premature neonates. However, no literature reports the anesthetic techniques, challenges, and risks associated with this procedure in this population. Aim: This study documents the anesthetic challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“… 11 In a cohort of neonates weighing <3 kg, Hubbard et al found that 40% of patients intubated for the purpose of the procedure required ongoing mechanical ventilation after TC. 33 We demonstrated a lower rate of mechanical ventilation among patients undergoing TC overall (19.3%).…”
Section: Discussionmentioning
confidence: 67%
“… 11 In a cohort of neonates weighing <3 kg, Hubbard et al found that 40% of patients intubated for the purpose of the procedure required ongoing mechanical ventilation after TC. 33 We demonstrated a lower rate of mechanical ventilation among patients undergoing TC overall (19.3%).…”
Section: Discussionmentioning
confidence: 67%
“…Preterm infants and neonates should be transported in a warmed incubator, and if possible it should be considered to perform surgery in the NICU for high-risk patients ( 20 ). The interruption of prewarming also can result in hypothermia ( 39 ), and with an adequate prewarming protocol, hypothermia incidence can be reduced to 20% ( 10 ), even in preterm infants ( 40 ). Our study also showed that prewarming before induction of anesthesia could protect both infants and neonates suffering from intraoperative hypothermia, indicating that the prewarming management strategy should be implemented during the whole course of anesthesia and surgery or even during postsurgery recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective observational study by Hubbard et al 6 on anaesthetic management of catheter-based PDA closure in neonates weighing <3 kg indicates that the prevalence of postoperative hypothermia is 3%. Similar approaches to thermal care were used in our study, such as transportation in prewarmed transport incubators, limiting cold exposure by placement of intravenous catheter and endotracheal tube in the NICU, forced air warming device, as well as increasing ambient air temperature.…”
Section: Discussionmentioning
confidence: 99%